Desenvolvimento de jogo didático para tornar prático o uso das atividades que contribuem para a melhoria de processo : elevação da alvenaria estrutural - Mesquita, Victor Felix de (2014)
Construction companies seek improvements for their management systems. Therefore, they need to apply concepts, methods and lean techniques for the identification and subsequent elimination or reduction of activities that do not add value to the final product. In this context, there are activities that contribute to the improvement of construction processes. They are best practices that seek to eliminate factors that create interruptions in processes that occur at construction sites. The objective of this research was to develop a didactic game that helps managers to make practical the use of activities that contribute to the improvement of structural masonry construction process, to stimulate flow production continuity in construction sites and the elimination of wastes. The methodology was divided into two phases. The first was the literature review, and the second was divided into five stages related to field research, that involve the procedures required for the development and validation of the tool proposed in this research. For this, the following tasks were carried out: exploratory study, list of best practices, development, validation and application of a checklist; development of didactic game and its validation by the application in a group dynamics, primarily with researchers and later with the managers of three of the six construction sites researched. As a result of the preparation of the best practices list, it was found that the neglect of most of these activities could result in the occurrence of making-do and consequently in rework. The application of checklist showed that the managers use best practices in their daily. The application of the game confirmed the information observed in the field and provided an overview of the process by managers. From that emerged the main contribution of this study, which was the conclusion that the game is a teaching tool that can be used to train professionals in the identification of strengths and weaknesses related to management activities in construction process of structural masonry elevation. Thus, it is expected that managers look at the tool as a practical instrument to identify best practices in the construction process and that in the future the tool can be applied in other processes.